Guarding Privacy in the Digital Age: A Comparative Analysis of Data Protection Strategies in Indonesia and France - Natamiharja, Rudi; Setiawan, Ikhsan (Jambe Law Journal, 2024)
Personal data protection is a critical issue in the contemporary digital era, marked by a significant rise in data collection and processing by both governmental and private entities. Indonesia, with its recently enacted Personal Data Protection Law, faces substantial challenges in implementation and enforcement. In contrast, France, as an EU member state, adheres to the General Data Protection Regulation (GDPR), widely regarded as the global benchmark for data protection. This study employs a comparative analysis to examine the legal frameworks, enforcement mechanisms, and data subjects' rights in Indonesia and France. Data were gathered through an analysis of legal documents, policy reports, and case studies on regulatory implementation in both countries. The results reveal that while there are notable differences in regulatory approaches and specifics, both countries aim to safeguard individuals' data rights. France's GDPR provides a more comprehensive and structured framework, whereas Indonesia is in the nascent stages of developing and refining its data protection regulations.